Comparative Analysis Of Stock Price Dan Volume Before And During Covid-19 Pandemic At PT. Kalbe Farma Tbk - Rahma Gusmawati Tammu; Elisabet Pali; Resinta (Universitas Kristen Indonesia Toraja, 2022)
This study aims to analyze the comparison of stock prices and volume at PT. Kalbe Farma Tbk before and during covid-19 pandemic. Type of this research used is descriptive quantitative analysis. Data analysis techniques using Paired Simple T-Test with SPSS 25. Based on the results of the Paired Sample T-Test on the stock price of PT. Kalbe Farma Tbk can be concluded that the significance value is 0.733 (p > 0.05). So Hi is rejected, Ho is accepted, which means there is no significant difference to the stock price of PT. Kalbe Farma Tbk, before and during the covid-19 pandemic. Based on the results of the Paired Sample T-Test on the stock volume of PT. Kalbe Farma Tbk can be concluded that the significance value is 0.043 (p < 0.05). So, Hi is accepted, Ho is rejected, which means that there is a significant difference in share volume.